The Role of The Uterus in Poetry Rumah Rahim, Pada Pemilik Rahim, and Upacara by Oka Rusmini - Rizkiyatussalamiyah, Mudrikah; Muhshonatun Nisa; Pinkan Zahrah Ramadhani; Dian Hartati (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
Women play a crucial role in society because they have wombs that give birth to future generations of humans. However, the birth of children in Bali is still influenced by customs based on the father's line. This research was conducted to reveal the forms of feminism in the poems "Rumah Rahim", "On the Owner of the Womb", and "Ucearat" by Oka Rusmini, based on libertarian feminist studies which support Kate Mille's theory of sexual politics. The research uses descriptive qualitative methods. The data collection technique used was the technique of reading, listening and taking notes using documentation studies. The analyzed data is then presented descriptively. Research results: There are social norms that force women to play certain roles, giving rise to gender injustice, there is unfair treatment of women so that women's roles and rights are reduced, injustice towards women causes minimal appreciation.